KONTRIBUSI KESEJAHTERAAN GURU, SARANA PEMBELAJARAN, DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP MOTIVASI KERJA PADA GURU SMK SWASTA DI SALATIGA - HASYIM, FUAD (2011)
The objective of the research is to analyze and to test: 1) the contribution of teachers' welfare, school facilities, and leadership on teachers' motivation of private vocational schools teachers in Salatiga simultaneously; and 2) the contribution of teachers' welfare, school facilities, and leadership on teachers' motivation of private vocational schools teachers in Salatiga partially. The type of the research is survey research. The research was done in private SMK Schools in Salatiga. The population of the research is all of private SMK teachers in Salatiga consist of 398 teachers. The sample of the research are 196 respondents selected using proportional random sampling techniques. The data collection method is done using questionnaire and documents. The data analysis was done using multiple linear regression analysis with three predictors, F test, t test, and determination coefficient (R2 ). Based on the analysis, the research concludes that: 1) there is a significant contribution of teachers' welfare, school facilities, and principals' leadership on teachers' motivation simultaneously. It is demonstrated with the model analysis of F statistics yielded 65.956 that significant at α = 0,01. It indicates that teachers' welfare, school facilities, and principals' leadership simultaneously have significant contribution on teachers' motivation in private vocational schools in Salatiga. The determination coefficient (R2 ) yielded is 0.508. It indicates that teachers' welfare, school facilities, and principals' leadership simultaneously determine the variability of teachers' motivation of 50.8%. The remain 41.2% is determined by other variables beyond the model. The regression equation yielded is Y = 34.470 + 0.232 X1 + 0.443 X2 + 0.197 X3 + e. The positive marks (+) in the regression coefficients of X1, X2 and X3 indicate positive contributions. It means that the higher tinggi teachers' welfare, school facilities, and principals' leadership the higher the teachers' motivation; 2) there are significant contributions of teachers' welfare, school facilities, and principals' leadership on teachers' motivation in private vocational schools in Salatiga partially. It is demonstrated with the t statistic results yielded that significant at α = 0.05